JUAL BELI COHUNG OLEH PENGRAJIN DADAK MERAK REOG PONOROGO: BOLEHKAH MENURUT ISLAM? - Fadlila, Isna Nur (ULUL ALBAB Jurnal Studi Islam, 2017)
The focus of this study is to identify cohung (peacock carcass) sale by dadak merak reog craftsman in Ponorogo and to analyse the view of Indonesian Council of Ulama (Majelis Ulama Indonesia) at Ponorogo Regency on cohung transaction. This empirical study used qualitative method. Data sources cover interview with dadak merak craftsman and MUI at Ponorogo Regency as well as documentation and literature to answer the research problem. It results in two findings. First, cohung transaction by the craftsman is done to create the fierce of dadak merak and got on agreed price. Secondly, cohung sale according to MUI at Ponorogo regency has different reasons. It is permitted because the sale practice depends on the context that is to be used not for consumption, and assumed that it is not only as transaction but also as wage. It is forbidden to buy the carcass since peacock is preserved animal.